Production of membranes for filtration of biomolecules - Castilho, Pedro Henrique Barata (2018)
Plasmids are autonomously replicating entities that can be found in all bacterial species and contribute for bacterial adaption and evolution. The demand of highly purified biomolecules has triggered the development of new separation technologies. Herein, plasmid DNA (pDNA) purification process has been extensively investigated, in order to obtain highly purified molecules for gene therapy applications and DNA (deoxyribonucleic acid) vaccines. The purification of plasmid DNA is currently performed by different techniques, namely chromatography (anion-exchange, hydrophobic interaction, reversed phase, affinity and sizeexclusion), enzymatic and membrane processes. Membrane technology is a broad and highly interdisciplinary field, where process engineering, material science and chemistry meet to produce membranes that have a wide range of applications, such as water, biomolecules and plasmid DNA purification. Furthermore, membrane systems take advantage of their selectivity, high surface-area-per-unit-volume. Herein, the main goal was to produce membrane systems - electrospinning membranes: poly ε-caprolactone, polyethylene oxide and k-carrageenan; modified-nylon membranes: nylon membrane impregnated with agarose - in order to perform microfiltration and ultrafiltration processes, respectively. The produced membranes were characterized by Scanning Electron Microscopy, Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy and Energy Dispersive Spectroscopy. The water contact angles were also determined and the results obtained showed that the produced membranes presented a hydrophilic character, which is in agreement with the date previously described in literature. Porosity studies were also performed and the results demonstrated that the electrospun membranes have porosity around to 80% and the modified-nylon membranes have porosities of approximately 40%. These values can be considered to be very high, when comparing these membranes to conventional microfiltration and ultrafiltration membranes produced by phase inversion. The plasmid DNA rejection was determined on the membranes produced and the experimental results showed that the modified-nylon membrane presented rejection values up to 100%, depending on the imposed permeate flux, which is an attractive feature for its application on plasmid DNA purification by ultrafiltration. In respect to the electrospun membranes produced the observed rejections were found to be lower, up to 30%, which demonstrates that this membranes need to be optimized or modified (post-synthesis modification).